Comparative morphology, histology, and cytology of odontocete cetaceans prostates - Suárez-Santana, Cristian M.; Fernández, Antonio; Sierra, Eva; Arbelo, Manuel; Bernaldo de Quirós, Yara; Andrada, Marisa; Mompeo, Blanca; Pérez, Lilian; Blanco, Alfonso; Méndez, Aniceto; Espinosa de los Monteros, Antonio; Rivero, Miguel A. (The Anatomical Record, 2019)
© 2019 American Association for Anatomy The prostate is the only male accessory gland in cetaceans. However, little is known about this organ in these species. Anatomical and histological characteristics of the prostate have been described in only a few cetacean species, further, one study reported a high incidence of prostatic pathologies in cetaceans that may impair reproduction. The objective of this work was to describe and compare the morphological, histological, and cytological characteristics of the prostate in different odontocete cetaceans. To this end, the prostate glands of 47 animals from nine different species of cetaceans were macroscopically and microscopically studied. Members of the families Delphinidae, Ziphiidae, and Physeteridae were included. In general, the prostate appeared as a musculo-glandular organ with two distinct parts—the Corpus prostatae and the Pars disseminata prostatae. In the pygmy sperm whale (Kogia breviceps) and the Cuvier's beaked whale (Ziphius cavirostris), the prostate was a discrete gland with a small Corpus prostatae. Microscopically, the prostates of different delphinids species shared similarities; however, the prostate of the pygmy sperm whale revealed significant histological differences compared to those of the delphinids. Immunohistochemical analysis was performed using low- and high-molecular-weight cytokeratin, vimentin, and prostatic specific antigen commercial antibodies. Electron microscopy analysis was performed on the prostate of a bottlenose dolphin and the cytomorphological differences among the major epithelial components of the prostatic epithelium were described. Anat Rec, 2019. © 2019 American Association for Anatomy.